Blockchain and AI-Driven Framework for Measuring the Digital Economy in GCC - Julian Hoxha; Marsela Thanasi-Boçe (Ital Publication, 2024)
The rapid growth of the digital economy presents opportunities and challenges, particularly in the Gulf Cooperation Council (GCC) region, where economic diversification is essential. Accurate measurement of digital economic activity is crucial for developing effective policies and strategic decision-making. This study introduces a comprehensive Digital Economy Measurement (DEM) framework tailored for the GCC. The framework integrates blockchain technology for secure and transparent data management, FinGPT for advanced financial data analysis, and Conversational Agent (CA) for enhanced user interaction. The research methodology involves a step-by-step design, starting with identifying and categorizing relevant data sources, collecting data through APIs and web scraping, and utilizing smart contracts and oracles for validation and recording. The data is managed securely using decentralized storage solutions and regional nodes. We propose using FinGPT and CA to analyze data in-depth and extract valuable insights. User interaction is prioritized through CA, interactive dashboards, and natural language processing, which prioritize user interaction with interfaces tailored to GCC-specific languages and cultures. The study's contribution to the literature lies in its novel, integrated approach to measuring the digital economy in the GCC, addressing challenges related to data accuracy, privacy, and regulatory compliance. By leveraging blockchain, FinGPT, and CA, the DEM-GCC framework offers a robust and adaptable solution for understanding and fostering the region's digital economy. Doi: 10.28991/ESJ-2024-08-04-019 Full Text: PDF